2018
DOI: 10.14569/ijacsa.2018.090238
|View full text |Cite
|
Sign up to set email alerts
|

Machine-Learning Techniques for Customer Retention: A Comparative Study

Abstract: Nowadays, customers have become more interested in the quality of service (QoS) that organizations can provide them. Services provided by different vendors are not highly distinguished which increases competition between organizations to maintain and increase their QoS. Customer Relationship Management systems are used to enable organizations to acquire new customers, establish a continuous relationship with them and increase customer retention for more profitability. CRM systems use machine-learning models to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(6 citation statements)
references
References 45 publications
0
3
0
3
Order By: Relevance
“…The study found that decision trees achieved the highest accuracy, followed by naïve Bayesian, logistic regression, and linear discriminant analysis. These findings provide insights into the suitability of different machine learning techniques for predictive maintenance in the telecommunications industry [9].…”
Section: Related Workmentioning
confidence: 88%
“…The study found that decision trees achieved the highest accuracy, followed by naïve Bayesian, logistic regression, and linear discriminant analysis. These findings provide insights into the suitability of different machine learning techniques for predictive maintenance in the telecommunications industry [9].…”
Section: Related Workmentioning
confidence: 88%
“…According to Sabbeh [22], machine learning techniques were used to overcome customer churn challenges in the banking sector. The authors in [23] described a churn prediction model in the banking sector using Classification and Regression Trees (CART) and C5.0, and the results showed that the prediction success rate of the churn class by CART was higher than that of C 5.0.…”
Section: Traditional Machine Learning Methods For Churn Management In the Banking Sectormentioning
confidence: 99%
“…On the basis of a set of training data, SVM attempts to determine the optimal separating hyperplanes between examples of distinct classes by representing observations as points in a high dimensional space. New instances are represented in the same space and assigned to a class depending on their closeness to the dividing gap [12]. Bagging, also called Bootstrap aggregating, is an ensemble learning approach that helps in the improvement of performance and accuracy of a machine learning algorithm.…”
Section: -1-bagging Support Vector Machinementioning
confidence: 99%